1998
DOI: 10.1038/bjc.1998.122
|View full text |Cite
|
Sign up to set email alerts
|

2-(4-Aminophenyl)benzothiazoles: novel agents with selective profiles of in vitro anti-tumour activity

Abstract: Summary 2-(4-Aminophenyl)benzothiazole (CJM 126) elicits biphasic growth-inhibitory effects against a panel of oestrogen receptor-positive (ER+) and oestrogen receptor-negative (ER-) human mammary carcinoma cell lines in vitro, yielding IC50 values in the nm range. Substitutions adjacent to the amino group in the 2-phenyl ring with a halogen atom or methyl group enhance potency in sensitive breast lines (pM IC50 values). Transient biphasic dose responses were induced but rapidly eradicated after specific drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(98 citation statements)
references
References 12 publications
1
96
0
1
Order By: Relevance
“…The initial mean doubling time of control tumours was 2.9 days. A maximum-tolerated dose was not (Tables I and 2) in addition to breast (Shi et al, 1996) (Bradshaw et al, 1998 (Bradshaw et al, 1998). Therefore, a shared mechanism(s) of resistance is implied.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The initial mean doubling time of control tumours was 2.9 days. A maximum-tolerated dose was not (Tables I and 2) in addition to breast (Shi et al, 1996) (Bradshaw et al, 1998 (Bradshaw et al, 1998). Therefore, a shared mechanism(s) of resistance is implied.…”
Section: Resultsmentioning
confidence: 98%
“…GI50 values within the pM range were obtained in human breast carcinoma cell lines including MCF-7 oestrogen receptor-positive (ER+) and MDA 468 oestrogen receptor-negative (ER-) cell lines. In contrast, GI50 values > 30 gm were obtained when activity of the same compounds was examined in PC3 and DU 145 human prostate cell lines (Bradshaw et al, 1998).…”
mentioning
confidence: 87%
“…Compounds 3,6,8,10,11,12,16,18 and 20 were selected by NCI for 60 human tumor cell lines' anticancer screening test at single dose assay. In vitro single-dose anticancer assay was performed in full NCI 60 cell panel representing L, NSCLC, CC, CNSC, M, OC, RC, PC, and BC.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, it was found that, 2-(4-aminophenyl)benzothiazole derivatives inhibit cancer cell growth with nanomolar scale against a large panel of human cancer cell lines particularly against breast, colon and ovarian cell lines in in vitro anticancer screening program of the National Cancer Institute (NCI) with a characteristic biphasic doseresponse relationship 6,7 . Up to present, scientists Shi and Bradshaw have a series of studies on antitumor activity of some benzothiazole derivatives [8][9][10][11][12][13][14] . First, the original lead compound 2-(4-aminophenyl)benzothiazole (CJM 126, NSC34445), which was originally prepared as a synthetic intermediate in a program of screening for tyrosine-kinase inhibitors, was found to possess selective in vitro activity against MCF-7 breast carcinoma cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation